Application of Fractional Calculus in Genetic Algorithms, Transportation Systems and Robotics - Tenreiro Machado, J. A. (2019)
This article illustrates several applications of fractional calculus (FC). This paper investigates the use of FC in circuit synthesis, traffic systems and robot control.